Microalgae concentrates (paste) can be used as an alternative feed to replace live microalgae for aquaculture due to its nutritional value and convenience. However, the clumping of cells and negative buoyancy of algae concentrate can affect bivalve culture as bivalves only capture particles in suspension and ingest a certain size range of particles. This study investigated the effect of shaking and blending treatments on the preparation of food suspensions prepared from algae concentrates (Isoch - LUDI PARWADANI AJI (HAYATI Journal of Biosciences, 2012)
Microalgae concentrates (paste) can be used as an alternative feed to replace live microalgae for aquaculture due to its nutritional value and convenience. However, the clumping of cells and negative buoyancy of algae concentrate can affect bivalve culture as bivalves only capture particles in suspension and ingest a certain size range of particles. This study investigated the effect of shaking and blending treatments on the preparation of food suspensions prepared from algae concentrates (Isochrysis and Pavlova). The results indicated that the higher the shaking time (5, 10, and 15 times) or blending time (10, 30, and 60 seconds), the smaller was the diameter of the resulting algae particles. Moreover, the greater the volume of algae concentrate used in preparation, the larger the diameter of algae particles produced. Shaking may be the best option because it is cheaper and simpler. However, all the treatments provided a suitable particle size range for ingestion by bivalves.